Product Formula

 

Take a look at the compound angles formulas below:

      sin (A+B) = sinAcosB + sinBcosA

     sin (A - B) = sinAcosB - sinBcosA

     cos (A+B) = cosAcosB - sinAsinB

    cos (A - B) = cosAcosB + sinAsinB

 

we are going to prove some formulas from the above.

 

let A + B = X --------------------- (equation 1)

A - B = Y ------------------------ (equation 2)

 If we add (1) and (2)

 

            A + B + A - B = X + Y

           2A = X + Y

           A = \frac{X + Y}{2}

Also if we subtract (1) - (2)

           A + B - (A - B) = X - Y

           A + B - A + B = X - Y

          2B = X - Y

         B = \frac{X - Y}{2}

 

From equation (1)

             X = A + B

            sin X = sin (A+B)

            sin X = sinAcosB + sinBcosA

  but A = (X+Y)/2 and B = (X-Y)/2 

 

\sin X = sin \frac{X + Y}{2} \cos \frac{X - Y}{2} + \sin \frac{X - Y}{2} \cos \frac{X + Y}{2}

 

Also from (2) 

        Y = A - B 

        sin Y = sin (A - B)

        sin Y = sinAcosB - sinBcosA

        \sin Y = \sin \frac{X+Y}{2} \cos \frac{X-Y}{2} - \sin \frac{X-Y}{2} \cos \frac{X+Y}{2}

 And 

      cos X = cos(A+B)

     cos X = cosAcosB - sinAsinB

     \cos X = \cos \frac{X+Y}{2} \cos\frac{X-Y}{2} - \sin \frac{X+Y}{2} \sin\frac{X-Y}{2}

and lastly

          cos Y = cos (A-B)

         cos Y = cosAcosB + sinAsinB

        \cos Y = \cos \frac{X+Y}{2} \cos\frac{X-Y}{2} + \sin \frac{X+Y}{2} \sin\frac{X-Y}{2} 

 

from the above proofs,

sinX + sinY = [\sin \frac{X + Y}{2} \cos \frac{X - Y}{2} + \sin \frac{X - Y}{2} \cos \frac{X + Y}{2}] + [

\sin \frac{X+Y}{2} \cos \frac{X-Y}{2} - \sin \frac{X-Y}{2} \cos \frac{X+Y}{2}]

 

                                    sinX +sinY = 2sin\frac{X+Y}{2}cos\frac{X-Y}{2} 

 

sinX - sinY = [\sin \frac{X + Y}{2} \cos \frac{X - Y}{2} + \sin \frac{X - Y}{2} \cos \frac{X + Y}{2}] - [

\sin \frac{X+Y}{2} \cos \frac{X-Y}{2} - \sin \frac{X-Y}{2} \cos \frac{X+Y}{2}]

 

sinX - sinY = \sin \frac{X + Y}{2} \cos \frac{X - Y}{2} + \sin \frac{X - Y}{2} \cos \frac{X + Y}{2}

- \sin \frac{X+Y}{2} \cos \frac{X-Y}{2} + \sin \frac{X-Y}{2} \cos \frac{X+Y}{2}

 

                  sinX - sinY = 2sin\frac{X-Y}{2}cos\frac{X+Y}{2}

 

cosX + cosY = \cos \frac{X+Y}{2} \cos\frac{X-Y}{2} - \sin \frac{X+Y}{2} \sin\frac{X-Y}{2} + 

\cos \frac{X+Y}{2} \cos\frac{X-Y}{2} + \sin \frac{X+Y}{2} \sin\frac{X-Y}{2}

 

                cosX + cosY = 2 cos \frac{X+Y}{2} cos \frac{X-Y}{2}

 

cosX - cosY = \cos \frac{X+Y}{2} \cos\frac{X-Y}{2} - \sin \frac{X+Y}{2} \sin\frac{X-Y}{2} - [

\cos \frac{X+Y}{2} \cos\frac{X-Y}{2} + \sin \frac{X+Y}{2} \sin\frac{X-Y}{2}]

 

cos X - cos Y = \cos \frac{X+Y}{2} \cos\frac{X-Y}{2} - \sin \frac{X+Y}{2} \sin\frac{X-Y}{2}

- \cos \frac{X+Y}{2} \cos\frac{X-Y}{2} - \sin \frac{X+Y}{2} \sin\frac{X-Y}{2}

 

                             cosX - cosY = -2 sin \frac{X+Y}{2} sin\frac{X-Y}{2}

 

 

          Example

Express the following as product of trigonometrical ratios

 

           1.  sin 8x + sin 2x

           2.  cos 12x - cos 6x

          3.  sin 10x - sin 18x

          4.  cos 4x + cos 14x

 

        Solution

        1.     sin 8x + sin 2x = 2 sin \frac{X+Y}{2} cos \frac{X-Y}{2}

                                        = 2 sin \frac{8x+2x}{2} cos \frac{8x-2x}{2}

                                        = 2 sin \frac{10x}{2} cos \frac{6x}{2}

                                        = 2 sin 5x cos 3x

 

      2.    cos 12x - cos 6x = - 2 sin (X+Y)/2 sin (X-Y)/2

                                      = -2 sin (12x + 6x)/2  sin (12x - 6x)/2

                                      = -2 sin (18x)/2 sin (6x)/2

                                      = -2 sin 9x sin 3x

 

    3.    sin 10x - sin 18x = 2 sin (X-Y)/2 cos (X+Y)/2

                                     = 2 sin (10x - 18x)/2 cos (10x + 18x)/2

                                     = 2 sin (-8x)/2 cos (28x)/2

                                     = 2 sin (-4x) cos 14x

                                     = - 2 sin 4x cos 14x  

 

4.    cos 4x + cos 14x = 2 cos \frac{X+Y}{2} cos \frac{X-Y}{2}

                                  = 2 cos (4x + 14x)/2 cos (4x - 14x)/2

                                  = 2 cos 18x/2 cos -10x/2

                                 = 2 cos 9x cos -5x   

                                 = 2 cos 9x cos 5x

 

NOTE: unlike sin and tan, the cos of a negative number is same as the positive.. i.e.cos (-p) = cos p, cos (-2x) = cos 2x etc.

 

                    EXERCISE

Write the following as product of trigonometry ratios

 

      1.   sin 21t + sin 15t 

      2.   sin 18θ - sin 12θ 

     3.   cos 10α - cos 4α 

     4.   cos 6x - cos 2x

     5.   sin 3x + sin 5x

     6.   cos 28y - cos 36y

     7.   cos 5x + cos 9x 

     8.   sin 2B - sin 12B

     9.   sin 3p - sin 7p

    10.  cos 2θ - cos 8θ

 

NEXT: Product formula continuation

PRE: Compound angles 

 

PRE

NEXT

 

          

Leave a Reply

Your email address will not be published. Required fields are marked *